Pengaruh Risiko Sistematik, Leverage dan Profitabilitas Terhadap Koefisien Respon Laba - Awang Riza Vadilah; N.A. Rumiasih; Angga Prasetia (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The development of the capital market in Indonesia requires the availability of high-quality financial information, particularly earnings, as a basis for investors’ decision-making. The market’s reaction to earnings information is reflected in the earnings response coefficient (ERC), which is influenced by various factors such as systematic risk, leverage, and profitability. This study aims to analyze the influence of systematic risk, leverage, and profitability on the earnings response coefficient for companies operating in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2022–2023 period. This study employs a quantitative approach with an associative research design. The study population consists of all companies in the consumer goods industry sector on the Indonesia Stock Exchange, with a purposive sampling technique yielding 48 samples. The data used are secondary data in the form of annual financial reports. Data collection was conducted through documentation, while data analysis was performed using multiple linear regression with SPSS, along with classical assumption tests. The results indicate that systematic risk does not have a significant effect on the earnings response coefficient. Meanwhile, leverage and profitability have a significant positive effect on the earnings response coefficient. Simultaneously, all three variables have a significant effect on the earnings response coefficient (ERC). This study concludes that investors pay more attention to internal firm factors such as leverage and profitability than to systematic risk when responding to earnings information. Consequently, firms need to improve their financial performance to elicit a positive market response.